Current progress in strategies to profile transcriptomic m6A modifications - Yang, Yuening; Lu, Yanming; Wang, Yan; Wen, Xianghui; Qi, Changhai; Piao, Weilan; Jin, Hua (Frontiers in Cell and Developmental Biology, 2024)
Various methods have been developed so far for detecting N 6 -methyladenosine (m 6 A). The total m 6 A level or the m 6 A status at individual positions on mRNA can be detected and quantified through some sequencing-independent biochemical methods, such as LC/MS, SCARLET, SELECT, and m 6 A-ELISA. However, the m 6 A-detection techniques relying on high-throughput sequencing have more effectively advanced the understanding about biological significance of m 6 A-containing mRNA and m 6 A pathway at a transcriptomic level over the past decade. Various SGS-based (Second Generation Sequencing-based) methods with different detection principles have been widely employed for this purpose. These principles include m 6 A-enrichment using antibodies, discrimination of m 6 A from unmodified A-base by nucleases, a fusion protein strategy relying on RNA-editing enzymes, and marking m 6 A with chemical/biochemical reactions. Recently, TGS-based (Third Generation Sequencingbased) methods have brought a new trend by direct m 6 A-detection. This review first gives a brief introduction of current knowledge about m 6 A biogenesis and function, and then comprehensively describes m 6 A-profiling strategies including their principles, procedures, and features. This will guide users to pick appropriate methods according to research goals, give insights for developing novel techniques in varying areas, and continue to expand our boundary of knowledge on m 6 A.